Effects of achievement goals on learning interests and mathematics performances for kindergarteners - Wu, Chung Chin (Frontiers in Psychology, 2023)
Studies have investigated effects of achievement goals on learning interests and mathematics performance above elementary-school level. However, few studies have explored this topic among kindergarteners based on sound theoretical frameworks. Through the enrollment of 15 kindergarten teachers and 180 kindergarteners, this study revalidated newly developed measurements of kindergarteners’ achievement goals and learning interests and used these measures to further clarify the effects of achievement goals on learning interests and mathematics performances using structural equation modeling. The results indicate: (1) Task-approach goals have positive effects on situational interest and advanced arithmetic performance, whereas task-avoidance goals have positive effects on individual interest. (2) Self-based goals have null effects on most learning interests and mathematics performance, but they have significant negative effects on numbering and counting performance. However, most of these null effects represent negative tendencies. (3) Other-approach goals have positive effects on situational interest and basic arithmetic performance, whereas other-avoidance goals have null effects on these outcomes but have an almost significant positive effect on numbering and counting performance. (4) Task-based goals and self-approach goals are generally beneficial for learning interests and mathematics performance. These results suggest that task-based goals and other-approach goals may be implemented with consideration of potential long-term detrimental effects of social comparison on learning outcomes. Further, possible negative effects of self-based goals must be monitored to prevent them undermining learning outcomes. This study revealed consistent, inconsistent, and new evidence that respectively verifies, complements, and contradicts findings on the learning outcomes of students above elementary-school level.